Aboriginal land claim to Lakefield National Park - Queensland. Land Tribunal (Brisbane, Qld. : The Tribunal, 1996)
Findings, recommendations and advice; land claim procedures and statutory criteria; evidence of historical association from archaeological research, explorers documentation, genealogies and family histories; evidence of traditional affiliation by claimants Kuku Thaypan, Lamalama group and separate clans through spiritual association and rights and responsibilities to land.
Includes bibliographical references.
Keywords: Aboriginal Australians -- Queensland -- Lakefield National Park -- Land tenure; Land tenure -- Queensland -- Lakefield National Park; Gugu Warra / Koko Wara people (Y80) (Qld SD55-13); Umbuygamu / Morrobalama people (Y55) (Qld SD54-12); Land rights - Conservation areas; Umbindhamu people (Y50) (Qld SD54-08); Guugu Yimidhirr / Gugu Yimithirr / Kuku Yimidhirr people (Y82) (Qld SD55-13); Kuku Thaypan / Gugu Dhayban people (Y84) (Qld SD54-16); Wurangung people (Y66) (Qld Sd54-12); Gugu Rarmul / Rarmul people (Y71) (Qld SD54-16); Culture - Relationship to land; Ayabadhu people (Y60) (Qld SD54-12); Aghu-Tharnggala people (Y65) (Qld SD54-12); Sites - Ceremonial grounds; Law - Land - State and Territory - Queensland; Land rights - Claims, disputes, hearings; History - Genealogy and family history; Lakefield National Park (Qld.); Lakefield (Qld SE Cape York SD55-09)